Association between pregnancy and pregnancy loss with COPD in Chinese women: The China Kadoorie Biobank study - Sha Huang; Jia Yi Hee; Yuxun Oswald Zhang; Ruofan Gongye; Siyu Zou; Kun Tang (Frontiers Media S.A., 2022)
BackgroundChronic obstructive pulmonary disease (COPD) is an inflammatory lung disease characterized by airflow blockage. Pregnancy and pregnancy loss may be related to an elevated risk of COPD, although studies have yet to report on this association. Hence, this study aims to investigate the association between pregnancy and pregnancy loss with the risk of COPD among Chinese women.MethodsData on 302,510 female participants from the China Kadoorie Biobank were utilized for this study. Multivariable logistic regression, stratified by sociodemographic and lifestyle factors, was employed to obtain the odds ratio (ORs) and 95% confidence intervals (CIs) for the association between pregnancy and pregnancy loss with COPD.ResultsPregnancy loss was significantly associated with increased risk of COPD (OR 1.19, 95% CI 1.13-1.25), specifically, spontaneous (OR 1.19, 95% CI 1.11-1.29) and induced abortion (OR 1.18, 95% CI 1.12-1.25). Stillbirth, however, was not significantly associated with the risk of COPD (OR 1.09, 95% CI 0.99-1.20). Increasing number of pregnancy losses was associated with increasing risk of COPD (one pregnancy loss: OR 1.14, 95% CI 1.07-1.21, two or more pregnancy loss: OR 1.25, 95% CI 1.17-1.32, and each additional pregnancy loss: OR 1.06, 95% CI 1.03-1.09). A single pregnancy was significantly associated with reduced risk of COPD (OR 0.75, 95% CI 0.59-0.97), although each additional pregnancy was significantly associated with increased risk of COPD (OR 1.03, 95% CI 1.01-1.04).ConclusionPregnancy loss, in particular, spontaneous and induced abortions are associated with increased risk of COPD among Chinese women. A single pregnancy, however, demonstrated protective effects.